Peningkatan Kapasitas Kelompok Wanita Tani Guyub Makmur Colomadu Melalui Pelatihan Pembuatan Dan Pemanfaatan Pupuk Organik Cair Dari Limbah Rumah Tangga - Arifah Husna; Mohamad Ihsan; Srie Juli Rachmawatie; Umi Nur Solikah (Institut Nalanda, 2023)
Liquid organic fertilizer is a type effectively increases of organic fertilizer that is very effective in increasing plant productivity. This fertilizer is made from organic materials such as animal manure, food scraps, and agricultural waste which are fermented to produce nutrients that are easily absorbed by plants. Therefore, farmers need training and assistance to manufacture and use liquid organic fertilizers that are cheap and easy to make. This community service aims to provide training and assistance to women farmer groups in manufacturing and using liquid organic fertilizer. This activity was carried out in Trowangsan Village, Rt 003/014, Malangjiwan, Colomadu, Karanganyar, Central Java. The Community Service activity will be held on June 24, 2023. This training will include an explanation of the benefits and methods of making liquid organic fertilizer that is easy and cheap, as well as the practice of making liquid organic fertilizer directly by members of farmer women's groups. Based on the observations of the service team, participants took part in the activity enthusiastically. The enthusiasm of the participants can be seen from the participants who actively ask questions and are interested in direct training on the manufacture of liquid organic fertilizer. The achievement of the goals and benefits of this service activity can be known through evaluation and monitoring in the form of assistance to participants. Assistance is carried out by monitoring the implementation and application of POC in KWT Guyub Makmur's farming activities.